769 Evaluating a clinic for Unaccompanied Asylum-Seeking Children (UASC): the importance of infectious disease screening and a holistic approach to care. (17th August 2022) - Pinto, Alexandra Cardoso; Seery, Paula; Foster, Caroline
Abstract : Aims: In the year ending March 2021, over 32400 individuals claimed asylum in the UK. Of those, 2044 (6%) were Unaccompanied Asylum-Seeking Children (UASC). UASC receive healthcare as a looked after child (LAC) through community paediatric services with a recommendation for communicable disease screening in national guidance. Emerging data suggest high levels of tuberculosis (TB) infection, blood born viruses (BBV), parasitic infections and mental health disorders. In response, a face-to-face (F2F) 'one-stop shop' infectious disease (ID) screening was implemented at St Mary's Hospital, London. The objectives were to evaluate the UASC screening programme, calculate infection prevalence and identify further health needs. Methods: Retrospective audit of electronic patient records for UASC attending ID screening from 01.11.19 to 19.10.21. Data collected included baseline demographics, social and mental health history, journey details, infection screening for TB, BBVs and sexually transmitted infections (STIs). Data was anonymised with median and interquartile ranges (IQR) summarising non-normally distributed continuous variables and numbers and percentages summarising categorical variables. Results: 120 UASC were referred; 89.2% (107/120) male, median age 17 (IQR 16-17). One went missing before being seen. 57.1% (68/119) are staying in supported accommodation and 36.1% (43/119) in foster care. Three commonest countries of origin included Sudan 26.1% (31/119); Eritrea 22.7% (27/119) Afghanistan 16.8% (19/119). A F2F interpreter was available for 59.7% (71/119) and phone interpreter for 21.8% (26/119). Median duration of travel to the UK (n=65) was 2 years (IQR 0.75–4), with 55.7% (54/97) arriving by road, 37.1% (36/97) by boat and 7.2% (7/97) by plane. The median time between UK arrival and screening (n=109) was 2 months (IQR 1-3). 44.5% (53/119) had screening results requiring recall or onward referral. [ table 1 ] 19.3% (23/119) reported being sexually active, however none of those testing positive for an STI disclosed prior consensual or non-consensual sex. 6.8% (8/117) chest x-rays were abnormal; pulmonary TB, 1 hilar lymphadenopathy (2: both determined not to be TB), cardiomegaly, 1 rib fracture, 1 parenchymal scarring with hyperinflation, 1 mild airway thickening, 1 mild perihilar peribronchial marking. 1 29.4% (35/119) reported issues with sleep, 39.5% (47/119) with mood. 28.6% (34/119) reported physical and 4.2% (5/119) sexual abuse. All patients accepted empirical antihelminth cover (albendazole 400mg) and 20000units of cholecalciferol once weekly for 12 weeks; median vitamin D level was 23.2nmol/L (IQR 18.0-32.3). Conclusion: This UASC clinic provides a thorough ID screening programme, following UK government and RCPCH guidelines. Nearly half of patients screened required follow-up with 1 in 10 having active infection (TB, HBV, HIV, STI) with public health implications for potential onward transmission. Diagnoses of highest prevalence were TB infection, followed by strongyloides. Non-judgmental routine STI screening is required as targeted screening based on history would have missed all STIs in this cohort. High reported rates of sleep and mood disturbance suggest high prevalence of mental health disorders and highlight the importance for liaison with community mental health services. Reducing barriers to holistic care with F2F interpreters, explaining UK medical confidentiality and entitlement to free NHS care is of great importance.